2014
DOI: 10.1016/j.rbr.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Análise da associação da fadiga com variáveis clínicas e psicológicas em uma série de 371 pacientes brasileiros com artrite reumatoide

Abstract: In this series of Brazilian patients with rheumatoid arthritis, we suggest a new significance for fatigue complains as an independent parameter not related with number of painful joints, disease or inflammatory activity scores. Psychological and functional impairments appear to be more related to fatigue. Additional studies and inclusion of standard measures for monitoring fatigue complains are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Cross-sectionally, univariate associations between depression and fatigue levels were uniformly significant, with a median correlation of 0.53 (range 0.29–0.77) [8, 16, 19, 22, 25, 27, 39, 40, 50, 56, 58, 64, 68, 75, 81]. The multivariate association remained significant after controlling for variables such as demographics, disease activity, pain and physical functioning in all studies [19, 25, 39, 40, 50, 75, 77] but one [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectionally, univariate associations between depression and fatigue levels were uniformly significant, with a median correlation of 0.53 (range 0.29–0.77) [8, 16, 19, 22, 25, 27, 39, 40, 50, 56, 58, 64, 68, 75, 81]. The multivariate association remained significant after controlling for variables such as demographics, disease activity, pain and physical functioning in all studies [19, 25, 39, 40, 50, 75, 77] but one [27].…”
Section: Resultsmentioning
confidence: 99%
“…Three cross-sectional studies reported a univariate significant association between anxiety and fatigue levels; correlations were 0.24 [22], 0.54 [16] and 0.55 [27]. The multivariate association between anxiety and fatigue after controlling for variables was significant in the two studies [27, 77].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on fatigue in RA have shown that patients consider their fatigue frustrating and exhausting and that it is much more related to pain intensity, depressed mood and nonrestorative sleep than to the inflammation itself and anemia 9,5153. For many patients, fatigue is not a disorder, but something expected and normal in their daily routine 54,55…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a frequent complaint in patients with arthritis, which they correlate to tiredness 9,10. In humans, fatigue is more central than peripheral, as well as being more psychological than physiological and thus is very difficult to quantify 11,12.…”
Section: Introductionmentioning
confidence: 99%
“…supervisionado a fim de manter a estabilidade articular, o trofismo muscular, a força e a resistência muscular e minimizar o surgimento de fadiga 30. …”
unclassified